1984
DOI: 10.1063/1.864795
|View full text |Cite
|
Sign up to set email alerts
|

Linear longitudinal oscillations in collisionless plasma diodes with thin sheaths. Part I. Method

Abstract: A method is proposed for treating linear longitudinal perturbations in one-dimensional collisionless plasma diodes with a uniform plasma region and thin electrode sheaths. The method is comprehensive in that it allows for very general equilibrium, initial, boundary, and external-circuit conditions. Upon Laplace-transforming the Vlasov and Poisson equations in both space and time, appropriate evaluation of all pertinent relations leads to a set of 2+2nσ(nσ is the number of particle species) coupled integral equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…We note that up to now we have only considered conditions inside the discharge gap, and that the important parameter Φ L (the wall potential) is still unspecified. To determine it we need an 'external-circuit condition', i.e., a condition on the potential at the wall and/or the total current (per unit area) in external circuit (Kuhn 1984).…”
Section: External-circuit Conditionmentioning
confidence: 99%
“…We note that up to now we have only considered conditions inside the discharge gap, and that the important parameter Φ L (the wall potential) is still unspecified. To determine it we need an 'external-circuit condition', i.e., a condition on the potential at the wall and/or the total current (per unit area) in external circuit (Kuhn 1984).…”
Section: External-circuit Conditionmentioning
confidence: 99%
“…26,27 In our case ͑in the waveguide cavity, say͒ this capacitor term is absent, being discarded by the boundary condition E z (rϭR)ϭ0.…”
Section: ͑10ј͒mentioning
confidence: 99%
“…To cope with realistic plasma devices the model has to be extended in various directions to include ion dynamics, collisions with neutrals, and the influence of boundary sheaths. Much work in this area has already been done by Kuhn [10,11] who reported that Q-machine equilibria in the limiting case of thin electrode sheaths are Pierce-unstable in a very broad range of operating conditions. This is, however, in contradiction with experience where stable plasma states are often observed.…”
Section: Introductionmentioning
confidence: 99%